Researching in Times of Crisis: Toward Information‐Resilient Societies. Issue 1 (14th October 2022) - Radford, Marie L; Connaway, Lynn Silipigni; Rorissa, Abebe; Ekmekcioglu, Cansu; Caidi, Nadia
Abstract: This panel features four experts in Library and Information Science (LIS) research who will present findings from major projects conducted during the COVID‐19 pandemic from national and international contexts. These include: a) a mixed‐methods study of virtual reference services in academic libraries during the pandemic's beginning, b) semi‐structured interviews with 29 global library leaders about library models that emerged in response to changes caused by the pandemic, c) a questionnaire survey of information professionals from the Association of Research Libraries (ARL) regarding linked data technologies, and d) a mixed‐methods approach to study newcomers and (mis)information during the pandemic including in depth interviews and content and sentiment analyses of social media platforms. The panelists will describe obstacles and challenges encountered during the pandemic, and efforts to overcame these. They will provide an overview of major findings and share research‐based implications for building and maintaining information‐resilient societies.